Upaya Peningkatan Peran Apoteker Sebagai Relawan Kesehatan Pada Haul Guru Sekumpul Ke-19 Tahun 2024 - Ikhwan Rizki, Muhammad; Intannia, Difa; Wati, Helmina; Karim, Abdul; Ramadhan, Muhammad; Kumala, Dinna Fitria; Dharmawan, Robby; Silviana, Mega; Izma, Hayatun (Carmin: Journal of Community Service, 2024)
Haul Guru Sekumpul is an activity held every year. This activity involved approximately 25,000 volunteers. Pharmacists are involved as health volunteers who are placed at health posts. Pharmacists have managerial competence in pharmaceutical supplies and clinical pharmacy, so volunteer pharmacists focus on pharmacist practice at health posts. This community service aims to increase the role of pharmacists as Health Volunteers in Haul Guru Sekumpul activities. The volunteer pharmacist committee is the Indonesian Pharmacists Association from Kab. Banjar (PC IAI Banjar Regency). The stages of community service activities are coordination meetings with the Banjar District Health Service, recruitment of pharmacist volunteers, training of pharmacist volunteers, technical meetings, implementation of activities, and evaluation of activities. Implementation of the Haul Guru Sekumpul on Saturday-Sunday, January 13-14, 2024 in Sekumpul Village, Banjar Regency. There were 76 pharmacists involved who had gone through a recruitment, training, and technical meeting process. Pharmacist volunteer knowledge increased after participating in volunteer training from 63.40 to 73.96. The volunteer pharmacists involved were satisfied with the smoothness of the service, the committee's service, the committee's response, the benefits of training, and the benefits of technical meeting with a questionnaire score above 80. The conclusion was that pharmacists played a role in Haul Guru Sekumpul's activities as volunteer pharmacists at health posts.